Measuring the Quality of Service in the Financial Area of a Public University: Development and Validation of the Instrument - Víctor Manuel Alcantar Enríquez; Sonia Elizabeth Maldonado-Radillo; José Luis Arcos Vega (Universidad Autónoma de Baja California, 2014)
This research, consisting of a descriptive study with a non-experimental design, involved an analysis to determine the validity and reliability of an instrument composed of seventeen items aimed at assessing the quality of service in the financial area of a public university by means of four variables: tangibility, reliability, responsiveness and empathy. The methodological strategy included the design of the measuring instrument; verification of the validity of content and construct; and analysis of internal consistency by means of Cronbach's alpha. The instrument was applied to 152 users of the service, attaining a reliability coefficient of 0.943. The results show that with respect to specific concepts, the questions were clear; nevertheless we found it necessary to relocate items and rename variables, which resulted in a valid and reliable instrument for measuring the quality of service in the context under study.